Transmission of cochlear distortion products as slow waves: a comparison of experimental and model data - Vetešník, Aleš; Gummer, Anthony W (The Journal of the Acoustical Society of America, 2012)
There is a long-lasting question of how distortion products (DPs) arising from nonlinear amplification processes in the cochlea are transmitted from their generation sites to the stapes. Two hypotheses have been proposed: (1) the slow-wave hypothesis whereby transmission is via the transverse pressure difference across the cochlear partition and (2) the fast-wave hypothesis proposing transmission via longitudinal compression waves. Ren with co-workers have addressed this topic experimentally by measuring the spatial vibration pattern of the basilar membrane (BM) in response to two tones of frequency f(1) and f(2). They interpreted the observed negative phase slopes of the stationary BM vibrations at the cubic distortion frequency f(DP) = 2f(1) - f(2) as evidence for the fast-wave hypothesis. Here, using a physically based model, it is shown that their phase data is actually in accordance with the slow-wave hypothesis. The analysis is based on a frequency-domain formulation of the two-dimensional motion equation of a nonlinear hydrodynamic cochlea model. Application of the analysis to their experimental data suggests that the measurement sites of negative phase slope were located at or apical to the DP generation sites. Therefore, current experimental and theoretical evidence supports the slow-wave hypothesis. Nevertheless, the analysis does not allow rejection of the fast-wave hypothesis.
Keywords: biologické modely; Otoacoustic Emissions, Spontaneous; vibrace; Pitch Perception; lidé; Models, Biological; Cochlea; Fourier Analysis; Fourierova analýza; Vibration; Lasers; Perceptual Distortion; deformace percepce; lasery; vnímání výšky zvuku; interferometrie; otoakustické emise spontánní; kochlea; Interferometry; Humans